Kegiatan Ice Breaking Sebagai Konsentrasi Pelatihan Diklat Satpam Di Sukoharjo - Agatha Cahya Kusuma Wardani; Tiara Fadhilah Hasna Fadholi; Anniez Rachmawati Musslifah (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
Security Guard Training and Training in Sukoharjo faces challenges in increasing the effectiveness of learning and concentration of participants. The activity